2009
DOI: 10.1080/03043790903480316
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between time management skills and the academic achievement of African engineering students – a case study

Abstract: Poor academic success by African engineering students is currently experienced in many higher educational institutions, contributing to lower financial subsidies by local governments. One of the contributing factors to this low academic success may be the poor time management skills of these students. This article endeavours to explore this relationship by means of a theoretical literature review and an empirical study. Numerous studies have been conducted in this regard, but with mixed results. The case study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 17 publications
(16 reference statements)
2
26
2
3
Order By: Relevance
“…Findings from self-regulation studies further show self-monitoring to positively predict achievement, with those who are able to reflect on and regulate their learning typically obtaining better grades (e.g., Dermitzaki, Leondari, & Goudas, 2009;Perry et al, 2001; for findings concerning conceptual overlap with planning as a self-regulation strategy, see Nett, Goetz, Hall, & Frenzel, 2012). Although largely overlooked in recent educational psychology research, despite having been incorporated into multiple prominent theories of self-regulated learning (e.g., Pintrich, 2004;Zimmerman, 2000), scattered findings also show time management to typically correspond with better academic performance (MacCann, Fogarty, & Roberts, 2012;Swart, Lombard, & de Jager, 2010); a finding replicated in a recent metaanalysis showing time management to positively predict cumulative achievement outcomes (Richardson et al, 2012).…”
Section: Self-regulated Learning and Achievementmentioning
confidence: 99%
“…Findings from self-regulation studies further show self-monitoring to positively predict achievement, with those who are able to reflect on and regulate their learning typically obtaining better grades (e.g., Dermitzaki, Leondari, & Goudas, 2009;Perry et al, 2001; for findings concerning conceptual overlap with planning as a self-regulation strategy, see Nett, Goetz, Hall, & Frenzel, 2012). Although largely overlooked in recent educational psychology research, despite having been incorporated into multiple prominent theories of self-regulated learning (e.g., Pintrich, 2004;Zimmerman, 2000), scattered findings also show time management to typically correspond with better academic performance (MacCann, Fogarty, & Roberts, 2012;Swart, Lombard, & de Jager, 2010); a finding replicated in a recent metaanalysis showing time management to positively predict cumulative achievement outcomes (Richardson et al, 2012).…”
Section: Self-regulated Learning and Achievementmentioning
confidence: 99%
“…The development of the questionnaire was guided by several efforts, including a review of the recent literature on measuring the effectiveness of university intervention courses, insights gained from similar existing questionnaires and expert judgment of lecturers who participated in the development and administration of the course [4][5][6][7][8][9] . The questionnaire was tested for reliability (Cronbach α=0.91).…”
Section: Methodsmentioning
confidence: 99%
“…Five studies examined the time management behaviors and practices of specific populations using qualitative methodologies including the use of time diaries (Hessing, 1994;Ho, 2003;Kotter, 1980;Winter et al, 1993;Yoels & Clair, 1994). Twenty-seven studies examined time management behaviors or practices in relation to other variables such as academic achievement, stress, or creativity (Adams & Jex, 1997Alay & Koçak, 2002;Anand, 2007;Britton & Tesser, 1991;Burt & Kemp, 1994;Cemaloglu & Filiz, 2010;Claessens et al, 2004;Francis-Smythe & Robertson, 1999;Garcia-Ros et al, 2004;Hellsten & Rogers, 2009;Jex & Elacqua, 1999;Lahmers & Zulauf, 2000;Lang et al, 1990;Lay & Schouwenburg, 1993;Macan et al, 1990;Misra & McKean, 2000;Mpofu et al, 1996;Mudrack, 1997;Shahani et al, 1993;Simons & Galotti, 1992;Swart et al, 2010;Trockel et al, 2000;van de Meer, et al, 2010;Williams et al, 1995;Zampetakis et al, 2010). One study (Trueman & Hartley, 1996) compared the effectiveness of time management skills between mature and traditional entry university students.…”
Section: Empirical Studies Of Time Managementmentioning
confidence: 99%
“…However, there is much literature examining time in the education domain, specifically in reference to time and schools (e.g., Knight, 1989), time and school learning (e.g., Anderson, 1984;Bloom, 1965;Carroll, 1963), time management and study skills for students or student athletes (e.g., Carney, 1988;Crutsinger, 1994;Danyluk, 1985;Garcia-Ros et al, 2004;Gibbs, Some of the populations identified as requiring time management training programs include adults performing job searches (Lindgren, 2004), first year university students (Ho, 2003;Swart et al, 2010;van der Meer et al, 2010), at risk university students (Zinatelli et al, 2002), online students (Bocchi et al, 2004), adults and college students with diabetes (Wdowik et al, 2001), adolescents with exceptionalities (DiPipi-Hoy et al, 2009), and student athletes . Recent time management training programs are also taking advantage of technology for their delivery (e.g., Zinatelli et al, 2002).…”
Section: Who Uses Time Management?mentioning
confidence: 99%
See 1 more Smart Citation